Health professionals' knowledge about female genital schistosomiasis. A qualitative investigation in a schistosomiasis endemic area in South Africa - Ingvild Sommerfelt; Patricia Ndhlovu; Myra Taylor; Saloshni Naidoo; Pavitra Pillay; Hanne Haaland; Svein Gunnar Gundersen; Tsakani Furumele; Eyrun Floerecke Kjetland (Elsevier, 2023)
Female Genital Schistosomiasis (FGS) is a neglected tropical disease that affects the lives of millions of women living in endemic areas. The aim of this study was to identify South African healthcare professionals' perceptions and experiences of Female Genital schistosomiasis. This qualitative study took place in Ugu District, KwaZulu-Natal, South Africa, in one Community Health Centre and two Primary Health Care clinics. The purpose was to explore local healthcare professionals' views and knowledge on FGS in an area endemic for Schistosoma haematobium, referred to as bilharzia, or isichenene in isiZulu. The empirical findings collected through interviews and observations are discussed in relation to the well-established research on FGS. This project also took cognizance of the United Nations (UN) sustainability development goals (SDGs) with a focus on gender and sanitation, as well as control programmes to prevent schistosomiasis. The study showed that there was a multi-faceted gap in knowledge between local midwives and professional nurses' work-related knowledge and the medical research team. Among the main causes are skewed power relations, whereby the women affected by FGS often have low socioeconomic status in society while the higher power structures do not prioritize FGS. This leads to health professionals being in a "middle position" where they are responsible for community health but are governed by their training and the guidelines of the institution in which they are a part. Furthermore, the study showed the importance of culture since nurses and midwives consult with patients, as they are part of a framework where their role is constrained due to governmental policies, protocols for patient care and the local culture. To provide adequate health services for FGS patients, this study indicates that policy, female patient management protocols, curricula, post graduate training, clinical practice and schistosomiasis prevention programs should include FGS.